TATA, DURASI, DAN FREKUENSI DALAM NOVEL ORANG-ORANG PROYEK KARYA AHMAD TOHARI: (Analisis Struktur Naratif) - hartono, Hartono (LITERA, 2005)
This research study employs the theory of narrative structure by Seymour Chatman. The study aims to describe plot elements comprising kernel and satellite, arrangement, duration, and frequency available in Orang-orang Proyek, a novel by Ahmad Tohari. The subject of the study was Orang-orang Proyek (2002, the first impression), a novel by Ahmad Tohari, and the focuses were plot elements covering kernel and satellite, arrangement, duration, and frequency. The data were collected through reading and recording. The novel was read and reread and its discourse and sentential and sub-sentential units containing narrative elements were recorded. The data were analyzed using the descriptive qualitative technique. The research findings show that Orang-orang Proyek contains 44 kernels and 132 satellites. On the basis of its logical order, it reveals that causality order can be parallel with temporal order. Chronologically, the beginning of the story also results, though not directly, in subsequent events. From the relation between the past and the present, the novel shows a tendency that the analeptic occurring before the present was almost the same as that occurring after the present. The novel contains 20 external anachronisms, 18 mixed anachronisms, and 13 internal anachronisms. The duration includes, from the most to the least, scene, summary, distraction, pause, and ellipsis. The dominance of scene, followed by summary, shows that the narrator’s role in the story is very small; most parts of the story are expressed through dialogues among characters to make it more interesting. Singular events dominate frequency in the novel, followed by iterative frequency, multiple-singular frequency, and repetitive frequency. Dominant singular events make the novel more lively and interesting. Key words: narrative structure, arrangement, duration, and frequency